Improvement of a Continuous Ethanol Fermentation from Sweet Sorghum Stem Juice by Aeration and Product Recovery using a Gas Stripping Technique - Arthit Thani (Science Faculty of Chiang Mai University, 2019)
The effects of aeration on a continuous ethanol fermentation from sweet sorghum stem juice (230 g/l of total sugar) and product recovery using in situ gas stripping during the fermentation by Saccharomyces cerevisise NP 01 were investigated. The fermentation was carried out in a 2-litre fermenter at the dilution rate of 0.02 h-1, and the aeration rate was varied from 0 to 0.4 vvm. The highest ethanol concentration (PE, 80.32 g/l) and ethanol productivity (QP, 1.61 g/l.h) were obtained at an aeration rate of 0.20 vvm with sugar consumption (SC) and viable cell counts of 85.34% and 3.11´108 cells/ml, respectively. In the control experiment (no aeration), the PE of 72.51 g/l, QP of 1.45 g/l.h, SC of 75.23%, and a viable cell count of 1.61´108 cells/ml were obtained. Higher aeration rates (0.3-0.4 vvm) improved SC and viable cell counts, but the PE and QP values were reduced. Under an aeration rate of 0.2 vvm using a gas stripping system, the fermentation efficiency (PE and QP) was further enhanced by 15% compared to operation under the same conditions without gas stripping. The PE and QP values in the process with gas stripping were 92.49 g/l and 1.85 g/l.h, respectively, and the sugar was almost completely consumed.